2022
DOI: 10.12659/ajcr.935095
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic Optic Neuropathy After Administration of a SARS-CoV-2 Vaccine: A Report of 2 Cases

Abstract: Case series Patients: Male, 53-year-old • Male, 65-year-old Final Diagnosis: Ischemic optic neuropathy Symptoms: Visual acuity loss • visual field defect Medication: — Clinical Procedure: — Specialty: Ophthalmology Objective: Rare coexistence of disease or pathology Background: Since the start of vaccination efforts against COVID-19, several presumed secondary ocular events have been desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
(14 reference statements)
1
8
0
Order By: Relevance
“…NA-AION post-COVID-19 vaccination has rarely been reported. ( 43 , 44 , 45 , 46 , 47 , 48 ) All patients shared the clinical presentation of painless sudden vision changes either described as a blurring of vision or a visual field defect and all had unilateral involvement. The onset of visual symptoms was with-in 15 days from the vaccination, (1-15 days).…”
Section: Discussionmentioning
confidence: 97%
“…NA-AION post-COVID-19 vaccination has rarely been reported. ( 43 , 44 , 45 , 46 , 47 , 48 ) All patients shared the clinical presentation of painless sudden vision changes either described as a blurring of vision or a visual field defect and all had unilateral involvement. The onset of visual symptoms was with-in 15 days from the vaccination, (1-15 days).…”
Section: Discussionmentioning
confidence: 97%
“… 14 Specific ocular and neuro-ophthalmic adverse events include, eyelid edema, blepharospasm, corneal graft rejection, uveitis, episcleritis, scleritis, choroiditis, acute macular neuroretinopathy, acute zonal occult outer retinopathy, multiple evanescent white dot syndrome, Vogt-Koyanagi-Harada disease, central serous retinopathy, retinal vein occlusion, anterior ischemic optic neuropathy (arteritic and non-arteritic), Leber hereditary optic neuropathy, neuroretinitis, tonic pupil, Tolosa-Hunt syndrome, ocular motor cranial neuropathies, facial nerve palsy, myasthenia gravis, ophthalmic vein thrombosis and optic neuritis. 2 , 3 , 10 , 12 , 15 , 16 , 17 , 19 , 20 , 22 , 23 , 24 , 25 , 26 , 33 In a single center retrospective study from South Korea, 17 eyes from 16 patients who developed ocular disease within 1 to 7 days of receiving the COVID-19 vaccine had the following diagnoses: retinal vein occlusion (n-9 eyes), retinal artery occlusion (n-1 eye), uveitis (n=3 eyes), and angle-closure glaucoma (n=4 eyes). Twelve patients received the Janssen COVID-19 vaccine and 4 patients the Pfizer-BioNTech COVID-19 vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Optic neuropathy is suspected as one of adverse events of the COVID-19 vaccine, which includes ON associated with or without demyelinating CNS diseases [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ], NA-AION [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ], and NMOSD [ 8 , 9 ]. Lotan et al reviewed 14 case reports and 2 case series by electronic searches of the published literature regarding neuro-ophthalmological complications of COVID-19 vaccines and reported that optic neuritis was the most common, occurring in 61 of 76 cases (80.3%) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%